What does Germany expect to gain from hosting the 2006 Football World Cup - Macroeconomic and Regionaleconomic Effects - Gerd Ahlert (Gesellschaft für Wirtschaftliche Strukturforschung (GWS), 2005)
The paper will present some estimates of the potential macro- and regionaleconomic effects for the German economy from hosting the football world cup 2006. The results have been prepared in the years 2000 and 2001 using the sport-economic simulation model SPORT (Ahlert 2001). The model has a special focus on analyzing sport-economic activities and has been constructed within the framework of a research project financed by the Ministry of the Interior (Meyer & Ahlert, 2000). It is based on a sport-economic satellite account - a detailed sport-economic database in conformity with concepts and definitions of the S.A - which has been integrated into the German I.FORGE model. Its performance is founded on the I.FORUM philosophy (Almon 1991). The simulation results are based on a szenario which take into account the necessary investments for upgrading the stadium facilities in the venues of the event as well as the tourism expenditure of incoming world cup visitors during the event in 2006. The results will illustrate the importance of modelling sport-economic activities in deep sectoral and intertemporal detail. Besides the macroeconomic national effects, the paper explains, how these effects can be transmitted to the regional level of the German federal state level by the econometric model system LÄNDER. This model system is founded on the national accounts for Länder and specifies the economic development of every single of the 16 federal states in the context of the expected macroeconomic development calculated within the SPORT model on the national level (Meyer & Ahlert 2003). The results will show that it is possible to estimale the potential macroeconomic effects of the soccer World Cup 2006 on the national and regional level. Under favourable conditions - independent of the type of financing these necessary investments - the staging of the football World Cup positively influences income and employment.
Keywords: L83; 330; Germany; Football World Cup 2006; Macroeconomic and Regionaleconomic Effects